PEMANFAATAN KOLEKSI BAHAN PUSTAKA DI PERPUSTAKAAN SMPN 4 MANADO DALAM MENUNJANG KEGIATAN BELAJAR SISWA - Anita Runtuwene; Meiske M. Rembang; Titiek Mulianti (Halu Oleo University, 2024)
This research aims to determine the role of library managers or teachers at State Middle School (SMP) 4 in Manado City in utilizing library collections to support student learning activities. The model used in this research employs a descriptive qualitative method that can provide a detailed depiction of the actual conditions. The SMPN 4 Manado library has its own room with a collection of fiction and books according to the Merdeka Curriculum. The existing collection of books is not well arranged on bookshelves and is only arranged on tables, some are stacked on the floor. Another condition where users get hot quickly is because the room does not have a fan or AC. Existing deficiencies can be improved for the better, because the library management is committed to improving the library at SMP Negeri 4 Manado, but is hampered by support from the previous school principal. It was only then that the new principal had the intention to make the library better. The arrival of the research team also strengthened the principal's commitment to organizing the library.